Art as therapy - Botton, Alain de 1969- (The school of life (Phaidon), 2013)
Methodology. The seven functions of art. What is the point of art? What counts as good art? What kind of art should one make? How should art be bought and sold? How should we study art? How should art be displayed? - Love. Can we get better at love? What is it like to be a good lover? Attention to detail. Am I allowed to be turned on? How to make love last. Courage for the journey - Nature. Remembering nature. The importance of the south. Anticipating autumn. The sense of what is beautiful. The new artists of nature - Money. Art as a guide to the reform of capitalism. The problem of taste. The role of the critic in the education of taste. Towards an enlightened capitalism. Career advice from artists - Politics. What should political art aiming at? What is there to be proud of? Who should we try to become? A defence of censorship. And now... to change the world.